2000
DOI: 10.1007/pl00010062
|View full text |Cite
|
Sign up to set email alerts
|

Is Endovascular Treatment of Abdominal Aortic Aneurysms Less Invasive Regarding the Biological Responses?

Abstract: To compare the biological responses following an endoluminal repair and a conventional open repair of abdominal aortic aneurysm (AAA), 14 patients who underwent an endoluminal repair (endograft group) and 26 who underwent an open repair (open group) were investigated. As markers of biological responses, interleukin-6 (IL-6) and -8 (IL-8), granulocyte elastase (GEL), white blood cell count (WBC), and serum C-reactive protein (CRP) were all measured preoperatively as well as on postoperative days (POD) 1, 3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 12 publications
3
39
0
7
Order By: Relevance
“…Some authors recommended aggressive routine use of anti-inflammatory drugs while most others prefer a more conservative approach. 15,25 Akin et al 26 did not observe any clinical benefit of prolonging antibiotic treatment beyond the day of endovascular intervention in PIS patients. Bischoff et al 17 in a recent survey of vascular surgery departments in Germany reported that 71% of the vascular centers treated PIS with non-steroidal anti-inflammatory agents (NSAIDs).…”
Section: Discussionmentioning
confidence: 96%
“…Some authors recommended aggressive routine use of anti-inflammatory drugs while most others prefer a more conservative approach. 15,25 Akin et al 26 did not observe any clinical benefit of prolonging antibiotic treatment beyond the day of endovascular intervention in PIS patients. Bischoff et al 17 in a recent survey of vascular surgery departments in Germany reported that 71% of the vascular centers treated PIS with non-steroidal anti-inflammatory agents (NSAIDs).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, reduced plasma protease inhibitory activities have been reported in patients with abdominal aortic aneurysms. 53 Nevertheless, these studies focused on circulating blood markers 54 rather than on a role for leukocyte elastase released by PMNs trapped within the mural thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings should therefore be interpreted with caution. However, each patient was his or her own control within each group improving the statistical strength of this study, and the long follow-up adds new data to previous literature [28][29][30][31] in the field of inflammation after EVAR.…”
Section: Discussionmentioning
confidence: 76%
“…The reported incidence of PIS after EVAR varies widely between 14% and 60% [28], and both underestimation and lack of explicit criteria for this syndrome may account for this large variation [29]. Plasma levels of IL-6 have been shown to increase already on the first postoperative day, culminate at 24 h, and remain increased for at least 6 days [28][29][30][31]. The full duration of this postoperative increase in inflammatory mediators has to our knowledge not been fully established, however.…”
Section: Discussionmentioning
confidence: 99%